Health Warning Label Training for Nutritionists to Inform Dietary Attention for Customers - Pamuji, Wirawan; Eko Winarni; Husein Al Djoufrie (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Customer Dietary Attention is one of essential point of view provided by Doctors to give an energized motivation for Nutritionists about creating Health Warning Labels as the customers are able to state their purpose in considering the product nutrition’s as affected to the health required as follow. The Research applies Research and Development Instrumental method to develop how Discovery Strategy applied by Doctor to train Nutritionists as they could produce labels in provided description of Health Labels. Due that Health Consideration is a part of Life Essential the label is expected to inform a warning as a promotion for all customers to state a balance Nutrition for them